Bounded rationality revisited: Making sense of complexity in applied sport science - Robertson, S. J.; Joyce, D. (SportRxiv Preprints, 2019)
Sport science`s accelerated uptake of technology and the resultant data growth has enabled new light to be shed on many of its most complex problems. However, this in turn has led to varying interpretation of these problems and often disagreement across sport science disciplines. This article proposes that revisiting the theory of bounded rationality as it pertains to applied sport science can provide a framework for understanding, accepting and utilising this complexity in judgement and decision-making contexts. Bounded rationality contends that individuals who intend to make rational decisions are bound to make merely satisfactory choices, rather than maximizing or optimising ones. Here, the theory is discussed with respect to how it enables for differences in human judgements to be elucidated based on inter-individual variations in information sampling and processing. As data generated from technology in sport continues to grow, these differences are likely to continually increase. The systematic nature of the differences between humans and machines are also explained. Adoption of a bounded rationality approach in applied sports environments can help to understand why differences exist in the interpretation of some of sport science`s most complex problems, as well as provide a framework for progressing a collective understanding of these areas.